Microcephaly, short stature, and developmental delay associated with a chemotactic defect and transient hypogammaglobulinaemia in two brothers. Issue 4 (August 1986) - Say, B; Barber, N; Miller, G C; Grogg, S E
Abstract : Two brothers presented with unusual facial features, microcephaly, developmental delay, and severe postnatal growth retardation. They both developed eczema in infancy and have had recurrent infections. Additional physical findings in both boys included hypogonadism, flexion contractures, hypoplastic patellae, and scoliosis. Their facial similarity was striking with sloping foreheads, beaked noses, large, protruding ears, and micrognathia. Low levels of serum gammaglobulins and defective chemotaxis were present in both boys in infancy. The hypogammaglobulinaemia was transient and improved, reaching normal levels by 3 1/2 years and 15 months, respectively. Defective chemotaxis and recurrent infections have persisted to the present. Both parents were normal. The mode of inheritance was not clear, as both X linked and autosomal recessive patterns were possible. Although patients with congenital malformations who also had immunodeficiency have previously been reported, immune system abnormalities, especially those of a transient nature, may frequently go unrecognised.